Activation of the alpha(2B) adrenoceptor by the sedative sympatholytic dexmedetomidine - Yuan, Daopeng; Liu, Zhongmin; Kaindl, Jonas; Maeda, Shoji; Zhao, Jiawei; Sun, Xiaoou; Xu, Jun; Gmeiner, Peter; Wang, Hong-Wei; Kobilka, Brian K. (Nature Chemical Biology, 2020)
The alpha(2) adrenergic receptors (alpha(2)ARs) are G protein-coupled receptors (GPCRs) that respond to adrenaline and noradrenaline and couple to the Gi/o family of G proteins. alpha(2)ARs play important roles in regulating the sympathetic nervous system. Dexmedetomidine is a highly selective alpha(2)AR agonist used in post-operative patients as an anxiety-reducing, sedative medicine that decreases the requirement for opioids. As is typical for selective alpha AR agonists, dexmedetomidine consists of an imidazole ring and a substituted benzene moiety lacking polar groups, which is in contrast to beta AR-selective agonists, which share an ethanolamine group and an aromatic system with polar, hydrogen-bonding substituents. To better understand the structural basis for the selectivity and efficacy of adrenergic agonists, we determined the structure of the alpha(2B)AR in complex with dexmedetomidine and Go at a resolution of 2.9 angstrom by single-particle cryo-EM. The structure reveals the mechanism of alpha(2)AR-selective activation and provides insights into Gi/o coupling specificity.
CRIS-Team WoS Importer:2020-03-24